2012
DOI: 10.1021/ie202097y
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage VPSA Process for CO2 Capture from Flue Gas Using Activated Carbon Beads

Abstract: Carbon dioxide removal from flue gas with a two-stage vacuum pressure swing adsorption (VPSA) process, which uses activated carbon (AC) beads as the adsorbent, was investigated both theoretically and experimentally. First, single-column VPSA experiments were studied for CO 2 /N 2 separation with high CO 2 feed concentration. Then, a two-stage VPSA process composed two columns for each stage was designed, and the effects of different parameters were investigated. The first-stage VPSA unit operates with a four-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…Many researchers around the world are 7 currently working on CO 2 capture from flue gases. It has been potentially demonstrated that CO 2 can be captured using PSA [224][225][226][227] but more fundamental and long-term pilot plant studies are required to properly benchmark this technique against amines. Also, olefin-paraffin separation by adsorption was quite studied, but the energetic consumption of the separation by adsorption is still comparable to distillation [228].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers around the world are 7 currently working on CO 2 capture from flue gases. It has been potentially demonstrated that CO 2 can be captured using PSA [224][225][226][227] but more fundamental and long-term pilot plant studies are required to properly benchmark this technique against amines. Also, olefin-paraffin separation by adsorption was quite studied, but the energetic consumption of the separation by adsorption is still comparable to distillation [228].…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption equilibrium of the gases onto the solid is described by the Virial adsorption model, which presents the following extension of single component equilibrium to predict multi component systems [13][14][15][16]:…”
Section: Appendix Amentioning
confidence: 99%
“…Carbon materials such as activated carbon (Shen, Liu, Li, & Yu, 2012), CNT (Lu, Bai, Wu, Su, & Hwang, 2008) and multiwalled CNT (Gui, Yap, Chai, & Mohamed, 2013) can be used to capture CO 2 by physical adsorption. Activated carbon is the most widely investigated classes of adsorbents in previous studies (Shen et al, 2012).…”
Section: Carbon Materialsmentioning
confidence: 99%
“…Activated carbon is the most widely investigated classes of adsorbents in previous studies (Shen et al, 2012). Although the CO 2 uptake and selectivity of activated carbon are low at lower pressures, the low heats of adsorption and the stability of carbon adsorbents make them competitive for CO 2 capture from flue gas.…”
Section: Carbon Materialsmentioning
confidence: 99%